Study on elemental image generation algorithms for integral imaging 3D display systems - Akhter, Nasrin; Suchi, Nusrat Jahan; Afiunnahar (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.